A4NH 2020 annual report highlights: Flagship 1 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2021)
This includes three highlights document for Flagship 1 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Informing and shaping food systems thinking Highlight 2: Filling the food environment evidence gap Highlight 3: Supporting the development of food-based dietary guidelines for Ethiopia